Raw material selection for pulping and papermaking using TOPSIS multiple criteria decision making design. Issue 3 (2nd September 2013) - Anupam, Kumar; Lal, Priti Shivhare; Bist, Vimlesh; Sharma, Arvind Kumar; Swaroop, Vinay
<x xml:space="preserve">Abstract</x> General approach for determining the suitability of a feedstock for pulping and papermaking includes chemical‐morphological analysis, cooking experiments, pulp characterization, and physico‐chemical properties evaluation. This work attempts to simplify this raw material selection problem using a multi‐criteria decision making (MCDM) approach exclusively on the basis of chemical–morphological analysis. Technique for order preference by similarity to ideal solution (TOPSIS) has been applied to the decision making unit comprising chemical and morphological characteristics of three Eucalyptus and Leucaena varieties to evaluate and rank them according to preference for pulping and papermaking. The applicability of the proposed methodology has been illustrated through three examples collected from literature. Results obtained in this investigation are in confirmation of the results published in literature. It reveals that the proposed method is practical, feasible, and easy to apply for pulp and paper based raw material selection. © 2013 American Institute of Chemical Engineers Environ Prog, 33: 1034–1041, 2014